Linguistic and psychometric validation of Sinhala version of Menopause Specific Quality of Life questionnaire - Rathnayake, Nirmala; Alwis, Gayani; Lenora, Janaka; Mampitiya, Iresha; Lekamwasam, Sarath (National Science Foundation: Colombo, 2021)
Menopause Specific Quality of Life (MENQOL) questionnaire assesses the health related quality of life (HRQOL) of postmenopausal women (PMW). It includes 29 menopausal discomforts distributed among four main domains, namely, vasomotor, psychosocial, physical and sexual. This study was designed for linguistic validation of the Sinhala version of MENQOL questionnaire and evaluation of its psychometric properties. The Sinhala version of MENQOL questionnaire was adapted following a standard methodology of linguistic validation, including forward translation, backward translation, patient testing and proof reading. It was selfadministered among 200 PMW, aged 56.0±3.3 years, selected randomly from Galle, Sri Lanka, along with the previously validated Menopause Rating Scale (MRS). Two weeks after the previous administration, the MENQOL questionnaire was administered again among a sub-group of PMW (n=100) selected from the 200 PMW. Then, the psychometric properties including reliability and validity were evaluated. The MENQOL questionnaire showed a high test re-test reliability measured with intraclass correlation=0.98 (0.97-0.99). The global Cronbach’s alpha was 0.95, indicating higher internal consistency. Seven factors with Eigen value exceeding one, explaining 77.11% of cumulative variance, were observed in Factor Analysis with Principal Component Analysis. It showed more explanatory factor extraction. Strong significant positive correlation between MENQOL questionnaire score and MRS score (r=0.78, p<0.001) was observed, which confirms the concurrent validity. It was observed that the self-administered, 29 item, Sinhala version of MENQOL questionnaire is a reliable and a valid menopause specific tool with satisfactory psychometric properties. Therefore, MENQOL questionnaire can be recommended to measure the menopausal discomforts and HRQOL of Sinhala speaking Sri Lankan PMW.
Keywords: Linguistic validation; Menopause; Menopause specific quality of life questionnaire; Reliability; Validity